Banking sector depth and economic growth nexus: a comparative study between the natural resource-based and the rest of the world’s economies - Al-Moulani, Ali J.; Alexiou, Constantinos (Taylor & Francis, 2017)
This paper investigates the relationship between banking sector depth and long-term economic growth in the natural resource based economies vis-à-vis economies that are not dependent on natural resources. For the empirical investigation, a Generalised Method of Moments (GMM) estimator for dynamic panel-data models is adopted for 194 countries spanning the period 1964 to 2013. By using different measures of banking sector depth and economic growth, the investigation yields three key findings. First, the banking-growth relationship is non-linear and positive within certain levels of banking sector depth in both country groups. Second, the time lag between the change in the level of banking sector depth and the effect on economic growth is shorter in the natural resource-based countries than in the other countries. Finally, the total effect of banking sector deepening on long-term economic growth is weaker in economies with abundant natural resources than in the rest of the world.
Keywords: Economic growth; Financial sector depth; Natural recourse-based economies